Comparative Antimicrobial Activity of Bauhinia X Blakeana Linn. Leaves and Flowers: Comparative Antimicrobial Activity of Bauhinia X Blakeana Linn. Leaves and Flowers - Radhika, B. (International Journal of Pharmaceutical & Biological Archive, 2018)
Antimicrobial activity of methanolic extract of leaves and flowers of Bauhinia x Blakeana was resolved against Gram-positive and Gram-negative microscopic organisms. Streptomycin was utilized as reference principles for examination of action. It was discovered that fluid concentrate has antimicrobial activity against Escherichia coli and Lactobacillus leaves have good activity than flowers.